Sei sulla pagina 1di 11

L 2 (R) R

L 2 (R) = {f

: R C : |f| 2 R}

{V j } jZ L 2 (R)

V j V j+1 , j Z

f(x) V j ⇐⇒ f (2x) V j+1

f (x) V j ⇐⇒ f (2 j x) V 0

L 2 (R)

j+ ||f (x) f j (x)|| L 2 (R) = 0

lim

f(x) L 2 (R)

f j (x) f (x) V j jZ V j = L 2 (R)

jZ

V J =

φ(x) V 0 V j

φ(x) V 0 :

φ j,n (x) 2 2 j φ(2 j x n),

j, n Z j Z

   φ j,n (x) V j

φ j,n (x) nZ = V j

   φ j,n 1 (x), φ j,n 2 (x) = 0

  φ j,n (x), φ j,n (x) = 1

n Z

n 1 , n 2 Z, n 1 = n 2

n Z

{φ j,n (x) 2 2 j φ(2 j x n)} nZ V j

W j V j V j+1

V j+1 = V j W j , j Z

W j

V j W j V j + 1 V j L 2 ( R )

V j W j V j+1

V j W j V j + 1 V j L 2 ( R ) •

V j L 2 (R)

W j 1 W j 2 , j 1 , j 2 Z, j 1 = j 2

L 2 (R)

L 2 (R) =

jZ

W j

ψ(x) W 0 W j

ψ(x) W 0 :

ψ j,n (x) 2 2 j ψ(2 j x n), j, n Z j Z

   ψ j,n (x) W j

ψ j,n (x) nZ = W j

   ψ j,n 1 (x), ψ j,n 2 (x) =

  ψ j,n (x), ψ j,n (x) = 1

0

n Z

n 1 , n 2 Z, n 1 = n 2

n Z

{ψ j,n (x) 2 2 j ψ(2 j x n)} nZ V j

L 2 (R) j

L 2 (R) = V j

+

i=j

W i

f (x) L 2 (R)

f(x) = a j (n)φ j,n (x) +

nZ

+

i=j

nZ

d i (n)ψ i,n (x)

a j (n) = a j,n = f(x), φ j,n (x) =

+

ˆ f(x)φ j,n (x)dx =

−∞

+

ˆ f(x)φ j (x 2 j n)dx = [f (x) φ j (x)] x=2 j n

−∞

d j (n) = d j,n = f(x), ψ j,n (x) =

+

ˆ f(x)ψ j,n (x)dx =

−∞

+

ˆ f(x)ψ j (x 2 j n)dx = [f (x) ψ j (x)] x=2 j n

−∞

a j (n) V j j d j (n) W j j A j (x) j D j (x) j V j V 0

f(x) = a j (n)φ j,n (x)

nZ

j

A j (x) =

+

n=−∞

f(x), φ j,n (x) φ j,n (x) =

+

n=−∞

a j (n)φ j,n (x)

f(x), φ j,n (x) =

+

ˆ

−∞

f(x)φ j,n (x)dx =

+

ˆ f(x)φ j (x 2 j n)dx =

−∞

[f(x) φ j (x)] x=2 j n

A j (x) =

+

n=−∞

[f(x) φ j (x)] x=2 j n φ j,n (x)

f (x) φ j (x) 2 j

D j (x) =

+

n=−∞

f(x), ψ j,n (x) ψ j,n (x) =

+

n=−∞

[f(x) ψ j (x)] x=2 j n ψ j,n (x)

j + 1 V j+1 V j W j φ j+1 V j+1 φ j ψ j V j W j

φ j,n (x) = φ j (x 2 j n) =

+

k=−∞

φ j,k (x), φ j+1,n (x) φ j+1,k (x)

+

φ j,k (x), φ j+1,n (x) = ˆ

−∞

φ j,k (x)φ j+1,n (x)dx =

+

ˆ

−∞

φ j (x 2 j n)φ j+1 (x 2 (j+1) k)dx =

[φ j (x) φ j+1 (x)] x=2 (j+1) (2nk)

+

φ j (x) φ j+1 (x) = ˆ

−∞

φ j (x)φ j+1 (ξ x)dx =

ˆ

+

−∞ φ(2 j x)φ(2 j+1 (ξ x))dx = ˆ

−∞

+

φ(2 1 α)φ(2 j+1 ξ α)=

ˆ

+

−∞ φ 1 (α)φ(2 j+1 ξ α)= [φ 1 (α) φ(α)] α=2 j+1 ξ

φ j,k (x), φ j+1,n (x) = [φ j (x) φ j+1 (x)] x=2 (j+1) (2nk) =

[[φ 1 (α) φ(α)] α=2 j+1 x ] x=2 (j+1) (2nk) =

[φ 1 (α) φ(α)] α=2 j+1 (2 (j+1) (2nk)) =

[φ 1 (α) φ(α)] α=2nk

h(x) = φ 1 (x) φ(x)

φ j,n (x) =

+

k=−∞

φ j,k (x), φ j+1,n (x) φ j+1,k (x) =

+

k=−∞

h(2n k)φ j+1,k (x)

ψ j,k (x), φ j+1,n (x) = [ψ 1 (α) φ(α)] α=2nk

 

+

ψ j,n (x) =

g(x) = ψ 1 (x) φ(x)

ψ j,k (x), φ j+1,n (x) φ j+1,k (x) =

k=−∞

+

k=−∞

g(2n k)φ j+1,k (x)

A j (x) j j + 1 A j+1 (x) V j

A j (x) =

+

n=−∞

A j+1 (x), φ j,n (x) φ j,n (x) =

n=−∞

+

k=−∞ a j+1 (k)φ j+1,k (x) , φ j,n (x) φ j,n (x) =

+

n=−∞

+

k=−∞ a j+1 (k) φ j+1,k (x), φ j,n (x) φ j,n (x)

+

φ j+1,k (x), φ j,n (x)

A j (x) =

n=−∞

+

k=−∞ a j+1 (k)h(2n k) φ j,n (x) =

+

+

n=−∞

[a j+1 (k) h(k)] k=2n φ j,n (x)

a j (k) A j (x) j a j+1 (k) A j+1 (x) j + 1

a j (k) = [a j+1 (k) h(k)] k=2n

j j + 1 A j + 1 ( x ) W j D j

j j + 1

A j+1 (x) W j D j (x) j

D j (x) =

+

n=−∞

A j+1 (x), ψ j,n (x) ψ j,n (x) =

+

n=−∞

=

[a j+1 (k) g(k)] k=2n

ψ j,n (x)

d j (k) D j (x) j a j+1 (k) A j+1 (x) j + 1

d j (k) = [a j+1 (k) g(k)] k=2n

A j+1 (x) j+1 j A j (x) D j (x)

A j (x) =

+

n=−∞

a j (n)φ j,n (x) =

n=−∞ a j (n)

+

k=−∞ h(2n k)φ j+1,k (x) =

+

n=−∞

+

k=−∞ a j (n)h(2n k)φ j+1,k (x) =

+

k=−∞

+

n=−∞ a j (n)h(2n k)φ j+1,k (x) =

+

k=−∞

+

n=−∞ a j (n)h(2n k) φ j+1,k (x)

+

h (n) h(2n)

A j (x) =

k=−∞ n=−∞

+

+

a j (n)h ( k

2

n) φ j+1,k (x) =

+

k=−∞ [a j (n) h (n)] n= k

2

φ j+1,k (x)

D j (x)

D j (x) =

+

n=−∞

+

d j (n)ψ j,n (x) = ··· = k=−∞ [d j (n) g (n)] n= k

2

g (n) = g(2n)

φ j+1,k (x)

A j+1 (x) = A j (x) + D j (x) =

+

k=−∞ [a j (n) h (n)] n= k

2

+ [d j (n) g (n)] n= k φ j+1,k (x)

2

j + 1 j h (n) g (n) h(n) g(n) h (n) g (n) h(n) g(n)

j + 1 j Φ

j + 1 j

j + 1 j Φ

Φ

Ψ Φ

Ψ Φ

Ψ Φ